Analisis Karakteristik dan Kualitas Butir Soal Ujian Semester Mata Pelajaran Pemeliharaan Mesin Sepeda Motor pada Siswa Kelas X SMK Rahmatullah Al Ma’arif 2022/2023 - Rindawan, Rindawan; Muhsan, Muhsan; Ikhsan, Muhamad (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
The purpose of this study was to determine the characteristics and percentage of even semester exam questions for class X in the motorcycle engine maintenance subject at SMK Rahmatullah Al Ma'arif. The research method used in this study is a survey method. The population in this study were all answers to the even semester exam questions for class X motorcycle engine maintenance subjects at Rahmatullah Al Ma'arif Vocational School in 2023. The data collection method in this study used the record survey method. The data collection instrument in this study is in the form of criteria. Processing the data used in this study using qualitative and quantitative item analysis techniques. The results showed that the characteristics of the Even Semester Examination Questions in the subject of motorcycle engine maintenance at SMK Rahmatullah Al Ma'arif 2022/2023 according to qualitative analysis needed improvement in material and construction aspects. Meanwhile, according to quantitative analysis, this question has good characteristics because it has a reliability coefficient alpha of 0.851; different power of good questions 0.225-0.545 as much as 60%; difficulty level 0.393-0.735 as much as 45%; and distractors function as much as 45% of the total questions. The results showed that the Even Semester Exam Questions for motorcycle engine maintenance subjects at SMK Rahmatullah Al Ma'arif 2022/2023 consisted of 55% of the items that were good and 45% of the items that were not good.